2016
DOI: 10.14260/jemds/2016/301
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Endometrial Curettings in Perimenopausal Women With Abnormal Uterine Bleeding

Abstract: BACKGROUNDAbnormal Uterine Bleeding (AUB) is one of the common complaints in the Gynaecology Outpatient Department. Endometrial sampling by dilatation and curettage is done to find out the aetiology of AUB in perimenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
1
1
1
Order By: Relevance
“…In Tukaram et al study functional causes contributed to 41 (55%) of cases and organic lesions contributed to 33 (45%) of cases. 16 In the study conducted by Singh et al PALM and COEIN accounted for 60% and 39.9% respectively unlike our study. 15 In the study conducted by Kalambe et al PALM contributed to 57.5% and COEIN to 42.5% cases.…”
Section: Resultscontrasting
confidence: 71%
“…In Tukaram et al study functional causes contributed to 41 (55%) of cases and organic lesions contributed to 33 (45%) of cases. 16 In the study conducted by Singh et al PALM and COEIN accounted for 60% and 39.9% respectively unlike our study. 15 In the study conducted by Kalambe et al PALM contributed to 57.5% and COEIN to 42.5% cases.…”
Section: Resultscontrasting
confidence: 71%
“…In the present study menorrhagia was the most common bleeding pattern which accounted for 65.5% which is comparable to 42.16% menorrhagia incidence reported by Jain M et al ,49% reported by Lotha et al,83.7% reported by Sreelakshmi U et al, 72% reported by Gupta et al ,45% reported by Das et al and 46.4% reported by Zeeba S et al[5][6][7][8] …”
supporting
confidence: 81%
“…Abnormal Uterine Bleeding (AUB) is defined as any uterine bleeding that is more than the normal volume, of longer duration and varying in regularity or frequency [1]. AUB is a collective terminology that includes both organic and non-organic causes.…”
Section: Introductionmentioning
confidence: 99%